The Trustworthy narrators whom Imam Ibn Maja was the only Scholar to Narrate about them compared with the other five books - Ali, Mustafa Mahmoud; Osman, Fadlan Mohamed (Journal of Islamic Sciences, 2018)
Sunan Ibn Maja is the book in written by Ibn Maja was famous due to this book. In this book, Ibn Maja classified the Prophet’s Hadeeth’s (Peace be upon him) and was the sixth book written to explain the Prophet’s Hadeeth’s. Ibn Maja’s book has received the attention of the Muslim’s scholars who wrote many works to explain it. Ibn Maja was the only scholar who explained many of the Prophet’s Hadeeth’s which were not explained in the previous five books. This is what made Ibn Maja’s book recognized and famous compared to the other five books. In addition, Ibn Maja’s book was the only book, which writes about many narrators whom are not mentioned in the previous five book. Some of them were considered as having absolute trustworthiness in their narration while the others were considered as trustworthy narrators but they were less than the absolute trustworthy narrators in their Hadeeth’s memorization. Despite the accurateness and trustworthiness of Hadeeth’s narration of Ibn Maja’s book. It was not from weak narrators and this was common for those narrators whom are not quite alert about Hadeeth’s accurateness when writing about them. This study aims to identify the number of the trustworthy narrators whom Imam Ibn Maja was the only scholar to narrate about them compared with the other five books, which documented by the memorizer Ibn Hajr and the Hadeeth’s narrated by him. The study concluded that Imam Ibn Maja was not only restricted to write about male narrators but female trustworthy narrators were also mentioned. The study concluded that the number of the accurate and correct Hadeeth’s narrated by those narrators was more than the number of weak Hadeeth’s.